Evaluation of the Influence of Risk Factors on the Time of Onset of Ulcers, Rest Pain, and New Gangrene Post-Angioplasty in Patients with Chronic Limb Threatening Ischemia (CLTI) at Dr. Cipto Mangunkusumo General Hospital - Effendi, Haikal; Suhartono, Raden; Kekalih, Aria (International Journal Labs, 2025)
Chronic Limb Threatening Ischemia (CLTI) represents the end stage of peripheral arterial disease, characterized by rest pain, ulcers, and gangrene. This study aims to evaluate the influence of metabolic risk factors—namely diabetes mellitus (DM), chronic kidney disease (CKD), and hypertension—on the timing of new symptom onset. This study employed a retrospective observational design involving CLTI patients who underwent successful angioplasty at RSUPN Dr. Cipto Mangunkusumo. Clinical data and the onset time of symptoms were collected and analyzed using univariate, bivariate, and multivariate logistic regression analyses. The study revealed a high prevalence of diabetes mellitus (89.3%, with 56% uncontrolled), hypertension (77.3%, with 41.3% uncontrolled), and chronic kidney disease (32%). Post-angioplasty symptoms included gangrene (33.3%), rest pain (24%), combined rest pain and gangrene (24%), and ulcers (18.7%), with a mean onset time of 80 ± 105 days. Uncontrolled diabetes mellitus (p=0.001; mean 39.46 days), hypertension (p=0.006; mean 54.81 days), and chronic kidney disease (p=0.001; mean 29.58 days) were significantly associated with accelerated symptom onset. Multivariate regression analysis identified hypertension as the strongest predictor (p=0.021; B=59.234; ?=0.273), followed by DM (p=0.027; B=40.693; ?=0.249) and CKD (p=0.036; B=30.234; ?=0.226), collectively explaining 53.9% of the variation in onset time. Uncontrolled DM was associated with increased incidence of ulcers and gangrene; hypertension with combined rest pain and gangrene; while CKD was more frequently associated with rest pain. These findings highlight the importance of aggressive risk factor management and structured post-angioplasty monitoring to delay symptom onset and reduce complications.